SENSE-SEAT: challenging disruptions in shared workspaces through a sensor-based SEAT - Ehrenberg, N.; Silva, J. L.; Campos, P. (12th International Conference on Tangible, Embedded, and Embodied Interaction, TEI 2018, 2018)
Creative industries' workers are becoming more prominent as countries move towards intellectual-based economies. Consequently, the workplace needs to be reconfigured so that creativity and productivity can be better promoted at shared workspaces. We report on a study based on diaries, interviews and probes, with 8 creative industries' professionals at a co-working space, with the goal of understanding their advantages and disadvantages, and causes for cognitive disruptions. Findings indicate that temperature, noise and coworkers' requests are the main causes for disruptions in the work processes. The insights are used to inform the design process of SENSE-SEAT, a seat with embedded sensors and tangible actuators, as a contribution to reimagining the role of tangible and embedded interaction in intelligent furniture. We are currently at a prototyping stage, with 3D prints and 3D renders and we explain the design process and outlining the early results.